2011
DOI: 10.1089/dna.2010.1112
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Blockage of Signal Transducer and Activator of Transcription 5 Signaling Pathway with Decoy Oligodeoxynucleotides Suppresses Leukemic K562 Cell Growth

Abstract: The protein signal transducer and activator of transcription 5 (STAT5) of the JAK/STAT pathway is constitutively activated because of its phosphorylation by tyrosine kinase activity of fusion protein BCR-ABL in chronic myelogenous leukemia (CML) cells. This study investigated the potential therapeutic effect of STAT5 decoy oligodeoxynucleotides (ODN) using leukemia K562 cells as a model. Our results showed that transfection of 21-mer-long STAT5 decoy ODN into K562 cells effectively inhibited cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…CD40 is a STAT1 target gene that is involved in T-cell activation, and suppression of its expression by the STAT1 ODN may account for the protective effects of the STAT1 ODN against atherosclerosis development 199 . Additionally, in a myelogenous leukaemia cell line (K562), treatment with a 21-bp ODN element containing a modified version of the GAS element that binds STAT5 suppressed STAT5 transcriptional activity, which led to cell cycle arrest and apoptosis 200 . This result suggests that blocking STAT5, which is downstream of the constitutively activated BCR–ABL, with an ODN decoy can be a promising therapeutic approach to overcome imatinib resistance in chronic myelogenous leukaemia 200 .…”
Section: Therapeutic Approaches That Target Stat Proteinsmentioning
confidence: 99%
“…CD40 is a STAT1 target gene that is involved in T-cell activation, and suppression of its expression by the STAT1 ODN may account for the protective effects of the STAT1 ODN against atherosclerosis development 199 . Additionally, in a myelogenous leukaemia cell line (K562), treatment with a 21-bp ODN element containing a modified version of the GAS element that binds STAT5 suppressed STAT5 transcriptional activity, which led to cell cycle arrest and apoptosis 200 . This result suggests that blocking STAT5, which is downstream of the constitutively activated BCR–ABL, with an ODN decoy can be a promising therapeutic approach to overcome imatinib resistance in chronic myelogenous leukaemia 200 .…”
Section: Therapeutic Approaches That Target Stat Proteinsmentioning
confidence: 99%
“…Alternative efforts to target STAT5B include the use of decoy oligonucleotides in chronic myeloid leukemia and potentially the use of siRNA. 70,71 In an experimental model of BCP-ALL, STAT5B gene expression was targeted by epigenetics-based therapy using BET bromodomain inhibitors. The study indicated that bromodomain inhibition induces apoptosis in vitro, improves survival in a xenograft model, and promotes downregulation of IL-7Ra.…”
Section: Jak/stat Targetingmentioning
confidence: 99%
“…To overcome this problem, the more stable short hairpin RNA (shRNA) was introduced using viral vectors and plasmids, which were then processed into siRNA [27] . Alternatively, the delivery of asODNs to target Stat5 isoforms do not suffer from nonspecifi c effects, although a two-fold greater molar excess is required compared with the corresponding siRNA to achieve effective knock-down [25,28] .…”
Section: Suppression Of Stat5 Using Oligonucleotide-based Strategies mentioning
confidence: 99%
“…Decoy ODNs have been established as an effi cient approach to block gene expression by competing with the binding of the transcription factor to the DNA cis-element [28,29] . This sequesters the transcription factor within the cytoplasm and prevents its target gene expression [30] .…”
Section: Suppression Of Stat5 Using Oligonucleotide-based Strategies mentioning
confidence: 99%
See 1 more Smart Citation